Cd(II) Complexes with Two New Ligands [2-thiophenecarboxaldehyde-4- phenylthiosemicarbazone and 4-methylbenzaldehyde-4-phenylthiosemicarbazone]: Synthesis, Spectral Characterization and Thermogravimetric Studies - Narayana Suvarapu, Lakshmi; Baek, Sung-Ok; Thogiti, Suresh (Letters in Organic Chemistry, 2016)
Background: We synthesized two new organic chelating agents, such as 2-thiophene carboxaldehyde-4- phenylthiosemicarbazone (TCPTSC) and 4-methylbenzaldehyde-4-phenylthiosemicarbazone (MBP TSC) and applied to chelation with Cd(II). Both the ligands (TCPTSC and MBPTSC) their Cd(II) complexes [(Cd-(TCPTSC-H)2) and (Cd-(MBPTSC-H)2)] are characterized by molar conductivity measurements, elemental analysis, FT-IR, 1H NMR spectroscopy, X-ray powder diffraction (XRD), and field emission scanning electron microscopy (FESEM). Initially the formation of TCPTSC and MBPTSC and their Cd(II) complexes is confirmed by FTIR. Thermogravimetric studies reveal the thermal stability of Cd(II) complexes over their ligands. The XRD and SEM studies reveal the change in crystal structure and morphology of both the TCPTSC and MBPTSC due to chelation with Cd(II). Methods: Molar conductivity measurements were carried out with conductivity portable meter Profiline Cond 3110 (WTW, a xylem brand, Germany). The FTIR spectra of TCPTSC and MBPTSC and their complexes were recorded on a Nicolet FT-IR 560 Magna spectrometer. Elemental analysis (N, C, H, and S) for TCPTSC and MBPTSC and their complexes was performed on Thermo Scientific elemental analyzer (Thermo Eager 300 Flash EA1112, Waltham, MA, USA). Powder XRD (PAN analytical X’pert PRO, Boulder, CO, USA) was carried out using CuKα (0.154056 nm) radiation at 40 kV and 30 mA. The data was collected between 10º and 60º 2 with a step size of 0.02º. The morphology of the crystals and powder was examined by FESEM (S-4200, Hitachi, and Tokyo, Japan). An ultra-thin layer of platinum was sputter-coated (E-1030 Ion Sputter, Hitachi, Japan) on the powder sample surface to improve the conductivity during the FESEM measurements. The 1H NMR spectra for both TCPTSC and MBPTSC and their complexes were obtained from NMR-vnmrs 600 instrument (Agilent, Santa Clara, CA, USA). Thermogravimetric analysis (DSC-TGA) was carried out in the temperature range of 25-800 ºC in nitrogen atmosphere and a heating rate of 10 ºC/min using SDT Q600 V20.9 Build 20 (TA instruments, Waters, USA). Results: The present study confirms the synthesis of new organic chelating agents, such as 2-thiophenecarboxaldehyde- 4-phenylthiosemicarbazone, 4-methylbenzaldehyde-4-phenylthiosemicarbazone. The chelation of these organic chelating agents with Cd(II) was also confirmed by various analytical techniques, such as elemental analysis, FT-IR, 1H NMR, XRD, and SEM. The thermogravimetric studies were performed to evaluate the thermal stability of free TCPTSC and MBPTSC and their Cd(II) complexes. The thermogravimetric studies reveal that the TCPTSC and MBPTSC lost over 97% weight at 800ºC whereas; the complexes still have a weight of 14-25%. Molar conductivity studies reveal that the complexes are neutral. The molar conductivity and elemental analysis studies predicted the tetrahedral geometry of both Cd(II) complexes. Conclusion: To evaluate more crystal studies of TCPTSC and MBPTSC and their complexes, single crystal studies are in progress. From the literature it was revealed that thiosemicarbazones and their metal complexes have biological activities, such as anti-bacterial, anti-fungal and anti-oxidants.
Keywords: Cd(II) complexes